Colloidal Stability of Magnetite Nanoparticles Coated by Oleic Acid and 3-(N,N-Dimethylmyristylammonio)propanesulfonate in Solvents - Li, Liu; Li, Decai; Zhang, Zhili (Frontiers in Materials, 2022)
In order to understand the factors affecting the colloidal stability in the carrier liquids of different ferrofluids, magnetite nanoparticles coated by surfactants 3-(N,N-dimethylmyristylammonio)propanesulfonate (DP) and oleic acid (OA) were fabricated as dispersions in diverse colloidal systems. The OA-coated magnetite could only be dispersed in the apolar carrier liquid (εr < 5), while DP-coated magnetite particles could establish a stable colloidal system in the polar base liquid (εr > 5) such as water and ethanol. The colloidal stability of OA-coated particles in the apolar solvents was mainly attributed to the steric repulsion of its outer thick liquid shell (∼3 nm). Due to the absence of steric repulsion on the solid thin shell (∼1 nm) on DP-coated magnetite, DP-coated particles could not be dispersed in the apolar liquid. In the polar liquid-based ferrofluids, DP-coated magnetite could form an electric double layer (EDL). The total Gibbs interfacial energy was analyzed based on Van Oss-Chaudhry-Good and DLVO theory to describe the behaviors of coated particles in solvents. In the case of neutral (pH = 7) water-based colloidal, DP-coated magnetite could establish an energy barrier of ∼2.2 kBT to prevent the particles from precipitation. Bare magnetite particles could form a relatively fragile colloid in a water system with an energy repulsion of ∼1.2 kBT. In contrast, OA-coated magnetite exhibited a severe phase separation in a water-based colloidal system due to its net attraction ∼ −1.3 kBT.